2013
DOI: 10.2478/s11535-013-0261-2
|View full text |Cite
|
Sign up to set email alerts
|

Do novel cement-type biomaterials reveal ion reactivity that affects cell viability in vitro?

Abstract: Calcium phosphate bioceramics have been studied as bone filler materials for years and have become a component of many commercial products. It is widely known that surface-reactive biomaterials may cause changes in the concentration of crucial ions in the surrounding environment, thereby affecting cell metabolism and viability. The aim of this study was to produce five cement-type biomaterials and characterize their phase composition using X-ray diffraction method, and porosity and pore size distribution using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…Magnesium has been reported to enhance osteoblast adhesion, increase angiogenesis in porous structures [ 24 ], increase bone formation [ 25 ] and increase bioresorption [ 26 , 27 ]. Crucially, in vitro, several papers have reported that high and low concentrations of Mg are inhibitory to cell proliferation and/or cytotoxic but optimal concentrations can enhance osteoblast proliferation and mineralization [ 28 , 29 ]. The findings of the current study support this but would suggest that this initial increase is transitory.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium has been reported to enhance osteoblast adhesion, increase angiogenesis in porous structures [ 24 ], increase bone formation [ 25 ] and increase bioresorption [ 26 , 27 ]. Crucially, in vitro, several papers have reported that high and low concentrations of Mg are inhibitory to cell proliferation and/or cytotoxic but optimal concentrations can enhance osteoblast proliferation and mineralization [ 28 , 29 ]. The findings of the current study support this but would suggest that this initial increase is transitory.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of ionic reactivity was performed based on a previously described procedure [2]. Briefly, granules sintered at various temperatures (90°C, 400°C, 800°C and 1150°C) were placed on a 24-well plate (200 mg per well) and sterilized using the ethylene dioxide method (1 h at 55°C with a subsequent degassation for 20 h).…”
Section: Evaluation Of Ionic Reactivitymentioning
confidence: 99%
“…Despite many advantages, the relatively rapid rate of in vivo gypsum resorption may disturb the rate of appropriate, gradual replacement of the biomaterial by the newly formed bone. Furthermore, due to the rapid resorption of gypsum and gypsum-based composites, the resulting calcium-rich fluid is relatively toxic for human osteoblasts [1,2]. The presence of OsteoSet® pellets (calcium sulfate bone void filler) caused a decrease in osteogenic cell proliferation [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cellular response to CPCs is linked to their phase composition [22]. The effect of chemical stability and resorbability of biomaterials, including ion release, on the cellular response was confirmed inter alia by Malafaya and Reis [23] and Przekora et al [10]. …”
Section: Introductionmentioning
confidence: 99%